Effectiveness of school-based nutrition education on obesity and nutritional status of adolescent girls: a scoping review - Iqbal, Sehar; Zafar, Saira; Shah, Syed Hassan Bin Usman; Ahmad, Abdul Momin Rizwan (Intelektual Pustaka Media Utama, 2025)
School based nutrition education is an effective way to improve nutritional status of adolescent girls through changing their dietary behaviors. This scoping review therefore aimed to summarize the available literature evaluating the effectiveness of school-based nutrition education interventions on anthropometric measures and nutritional status of adolescent girls. A systematic approach following the PRISMA guidelines was adopted to investigate the effects of nutrition education in schools. A search term and an eligibility criterion were applied and 2 databases, i.e., Scopus and PubMed were selected to retrieve the existing literature. After applying inclusion/exclusion criteria, a total of 11 studies and data from 3957 participants were included in this review. School-education intervention was taken as an independent variable to evaluate the effectiveness of the programs. Most of the studies found the beneficial effects of school-based nutrition programs to reduce obesity among adolescent girls. However, a few studies (n = 4) did not show any significant impact of nutrition education programs to improve nutritional status of this age-group girls. Our review reported the beneficial effect of school health-education programs to reduce obesity in adolescent girls. A holistic approach with more professional training for teachers based on health promotion strategies, inclusion of nutrition education into the curriculum, operative follow-up and evaluations are needed to implement more effective school-based nutrition education programs.